MASALAH DAN ALTERNATIF TEKNOLOGI PENGOLAHAN AIR UNTUK MASYARAKAT MISKIN KOTA - Herlambang, Arie (Jurnal Rekayasa Lingkungan)
Clean water to poor communities who live in crowded municipal area is stillexpensive and a luxury. This condition is evidenced by the number of people whouse ground water for their daily water, because water taps still seems expensivefor them. Diarrheal disease is still relatively high for Indonesia, where nearly 16thousand people suffer from diarrhea due to poor sanitation. To help the poor inthe city, there are several alternative technologies that can be applied to publicaccess to clean water and adequate low-cost, including ground water treatmenttechnology with a filter system equipped with an ultraviolet sterilizer, or ozonegenerators, or using ultrafiltration, if possible can also use the reverse osmosismembrane that for fresh water. Arsinum is the best alternative should be chosenfor fulfilled potable water in slump area.Keywords : Sanitation, water treatment technology, portable water, low-cost, slump area